Basosquamous carcinoma: Histopathological features - Nádia Lages Lima; Flaviana Dornela Verli; João Luiz de Miranda; Sandra Aparecida Marinho (Wolters Kluwer Medknow Publications, 2012)
Basosquamous carcinoma (BSC) is a rare aggressive epithelial neoplasm with features of both basal cell carcinoma and squamous cell carcinoma, with a tendency toward local recurrence and a propensity for lymph node and distant metastases. The aim of the present study was to report the case of a 63-year-old Caucasian male with BSC in the auricular region.